2008
DOI: 10.2139/ssrn.1313728
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of 'Public' Emergencies

Abstract: The paper seeks to clarify the notion of 'public emergency' and to address various theoretical misconceptions surrounding it. Public emergencies, I contend, are emergencies which interfere with the performance of a government's role and which, as a result, tend to have distinctive moral implications. Since their salient characteristics often vary markedly, I argue that one must pay close attention to them when assessing what responses they warrant. I use as my foil three leading theoretical approaches which I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Dealing with previous public emergencies such as Hurricane Katrina in New Orleans in 2005 was traditionally by disaster and crisis management (John 2009 ; Tanguay-Renaud 2009 ; Zack 2009 ). It is now suggested that an alternate route of inquiry which could be undertaken towards COVID is through existentialist philosophy (Vandekerckhove 2020 ).…”
Section: Managing Covid As Managers and As Leadersmentioning
confidence: 99%
“…Dealing with previous public emergencies such as Hurricane Katrina in New Orleans in 2005 was traditionally by disaster and crisis management (John 2009 ; Tanguay-Renaud 2009 ; Zack 2009 ). It is now suggested that an alternate route of inquiry which could be undertaken towards COVID is through existentialist philosophy (Vandekerckhove 2020 ).…”
Section: Managing Covid As Managers and As Leadersmentioning
confidence: 99%
“…regard to the first route, a bunch of papers on disaster management, published in 2009 in this journal, can form a useful scholarly basis to philosophically inquire into COVID-19 management. Tanguay-Renaud (2009) discusses public emergencies and asks what it is about an emergency that justifies 'emergency powers'. Reading that paper again I found it fascinating how, 11 years later, the framework and analysis set out by Tanguay-Renaud (2009) keeps its relevance effortlessly.…”
mentioning
confidence: 99%
“…Tanguay-Renaud (2009) discusses public emergencies and asks what it is about an emergency that justifies 'emergency powers'. Reading that paper again I found it fascinating how, 11 years later, the framework and analysis set out by Tanguay-Renaud (2009) keeps its relevance effortlessly. The author uses Hurricane Katrinaand its wrecking of New Orleans in 2005as a concrete example.…”
mentioning
confidence: 99%
See 2 more Smart Citations